2015
DOI: 10.1109/tuffc.2015.007018
|View full text |Cite
|
Sign up to set email alerts
|

Nonintrusive estimation of anisotropic stiffness maps of heterogeneous steel welds for the improvement of ultrasonic array inspection

Abstract: It is challenging to inspect austenitic welds non-destructively using ultrasonic waves because the spatially varying elastic anisotropy of weld microstructures can lead to the deviation of ultrasound. Models have already been developed to predict the propagation of ultrasound in such welds once the weld stiffness heterogeneity is known. Consequently, it would be desirable to have a means of measuring the variation in elastic anisotropy experimentally so as to be able to cor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Previous work has shown that stiffness maps from EBSD data are of more than sufficient resolution to allow refinement of model stiffness maps used to correct ultrasonic flaw detection signals (Mark et al ., ). Because the routines used to produce these model stiffness maps involve iterative correction, the requirements for the initial input maps are not stringent (Fan et al ., ). Angular agreement within 25° is acceptable so SRAS maps could be used as input data.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work has shown that stiffness maps from EBSD data are of more than sufficient resolution to allow refinement of model stiffness maps used to correct ultrasonic flaw detection signals (Mark et al ., ). Because the routines used to produce these model stiffness maps involve iterative correction, the requirements for the initial input maps are not stringent (Fan et al ., ). Angular agreement within 25° is acceptable so SRAS maps could be used as input data.…”
Section: Discussionmentioning
confidence: 97%
“…The predicted simple stiffness map, using the MINA model, matches the measured stiffness variation quite well, with some improvement desirable. A process to refine the MINA map was thus developed, which is discussed in [8].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 1(b) shows an example of a weld stiffness map made using recorded welding procedures and MINA parameters obtained from the macrograph of the weld [8].…”
Section: Stiffness Mapsmentioning
confidence: 99%
See 2 more Smart Citations